Biological and socio-cultural factors have the potential to influence the health and performance of elite female athletes: A cross sectional survey of 219 elite female athletes in Aotearoa New Zealand - Heather, A. K.; Thrope, H.; Ogilvie, M.; Sims, S. T.; Beable, S.; Milsom, S.; Schofield, K. L.; Coleman, L.; Hamilton, B. (Frontiers in Sports and Active Living, 2021)
Health is a pre-requisite for optimal performance yet the parameters which govern health and performance of elite female athletes are little understood. The aim of this study was to quantify the health status of elite female athletes, and understand sociocultural factors influencing that status. The survey addressed demographic, health and athletic performance history, training load, contraceptive use, sport-specific appearance and performance pressures, and communication barriers. Three hundred and fifty-seven elite New Zealand female athletes were recruited to complete an on-line survey. Two hundred and nineteen athletes completed the survey. Oligomenorrhea/amenorrhea had been diagnosed in only 12% of athletes compared with 50% of athletes not on hormonal contraception who reported symptoms consistent with this diagnosis. Stress fractures and iron deficiency were common and associated with oligomenorrhoea/amenorrhea (P = 0.002), disordered eating (P = 0.009) or menorrhagia (P = 0.026). Athletes involved in individual sports (P = 0.047) and with higher training volumes (P < 0.001) were more likely to report a medical illness. Seventy-three percent of athletes felt pressured by their sport to alter their physical appearance to conform to gender ideals with 15% engaging in disordered eating practices. Barriers to communicating female health issues included male coaches and support staff, and lack of quality information pertaining to health. Elite female athletes may fail to reach peak performance due to specific health issues and undiagnosed pathology. Sociocultural factors influence the effectiveness of support of female's health and performance. Organizational and cultural change is required if elite female athletes are to combine optimal health with best performance.